Temporary Layoffs and Unemployment Insurance: Is Experience Rating Desirable? - Julia Fath; Clemens Fuest (Center for Economic Studies and ifo Institute (CESifo), 2002)
This paper explores how the introduction of an experience rated system of unemployment insurance affects employment and welfare in a model where implicit contracts between firms and workers give rise to wage rigidities and unemployment. In the literature, it has been argued that experience rated systems of unemployment insurance may reduce long term employment as firms anticipate the higher costs of layoffs implied by experience rating. Our analysis shows that, despite the higher costs of layoffs, the introduction of experience rating may increase long term employment. Moreover, it unambiguously increases welfare.
Keywords: 330; unemployment insurance; labour markets; implicit contracts